App-based support for parental self-efficacy in the first 1,000 days: A randomized control trial - Outhwaite, Laura A. (Frontiers in Psychology, 2023)
Parental self-efficacy is key for guiding parents’ interactions with their child and is an important target for early intervention. This study reports a pilot randomized control trial (RCT) of a parenting application (app) with 79 parents of children aged 0–6 months in the United Kingdom. The app includes 1,026 daily age-appropriate activities across eight areas of child development, using resources accessible at home. While controlling for pre-test scores, parents who used the parenting app (Treatment Group) had significantly higher parental self-efficacy, after the 4-week intervention period, compared to the Active Control Group. Partial correlation analyses indicated that higher frequency of self-reported use of the parenting app was associated with greater parental self-efficacy outcomes. This evidence establishes proof of concept that parenting apps can have significant benefits on parental self-efficacy in early childhood. Limitations to the interpretation and generalization of the findings, as well as directions for future research are discussed.